The Implementation of Character Education in the High School of Catholic Seminary of St. Fransiskus Xaverius Kakaskasen Tomohon - Laatung, Fransika; Pangalila, Theodorus (Jambura Journal Civic Education, 2025)
This study aims to describe and analyse the implementation of character education in Catholic Seminary High School Kakaskasen Tomohon. This educational institution is a school for prospective priests that not only emphasises academic aspects, but also the formation of students' personality and spirituality through character education that is integrated in all school activities and boarding life. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that character education in Kakaskasen Catholic Seminary High School is implemented consistently through various indicators, including discipline, responsibility, simplicity and togetherness, integration of character values in learning, liturgical activities and spirituality, dormitory system, social activities, and personal example from educators and coaches. These values are formed through structured daily routines, community activities, value-based learning, and regular religious reinforcement. Evaluation of character education is carried out continuously through daily observations, monthly evaluation meetings between coaches, students' personal reflections, and personality reports every semester. The main strategies applied in character education in this school include exemplary behaviour, daily reflection and religious reinforcement. This finding strengthens the social learning and value clarification theories that place exemplary and internalisation of values in daily activities as the key to character building. This research is expected to be a reference for both religious and public schools in designing effective character education.